Здравствуй, Удмуртия - Грязев Георгий Геннадьевич (Удмуртия, 2016)
Экземпляры: аб. (20170606) / Инвентарный номер: 57324 / Цена: / Сис.шифр: 26.89(2Рос.Удм) / Авт.знак: З-46 / ГРНТИ: 39 / ББК: 26.89(2Рос.Удм)